Branched polyethylenimine-grafted-carboxymethyl chitosan copolymer enhances the delivery of pDNA or siRNA in vitro and in vivo - Park, Seong-Cheol (Dove Medical Press, 2013)
To generate a good carrier for gene transfection, O-carboxymethyl chitosan-graft-branched polyethylenimine (OCMPEI) copolymers were synthesized by increasing the weight percentage of branched polyethylenimine conjugated to the carboxyl groups of O-carboxymethyl chitosan. These spherical polyplexes with plasmid deoxyribonucleic acid (pDNA) or small interfering ribonucleic acid (siRNA) had diameters of ∼200–300 nm or ∼10–25 nm, respectively, and displayed significant transfection efficiency in normal and tumor cells. In particular, expression of green fluorescent protein (GFP) following pDNA transfection was effectively suppressed by delivery of GFP-specific siRNA with the same copolymer. The optimized copolymer and polyplexes were nontoxic in vitro and in vivo. The use of endocytosis inhibitors to investigate the mechanisms of transfection of the polyplexes suggested the involvement of macropinocytosis. An in vivo study in mice showed excellent GFP expression in the lung, kidney, and liver. The results demonstrated that the OCMPEI copolymer prepared in this study is a promising carrier for in vitro and in vivo gene delivery applications.